2000
DOI: 10.1093/hmg/9.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Human-mouse differences in the embryonic expression patterns of developmental control genes and disease genes

Abstract: Our understanding of early human development has been impeded by the general difficulty in obtaining suitable samples for study. As a result, and because of the extraordinarily high degree of evolutionary conservation of many developmentally important genes and developmental pathways, great reliance has been placed on extrapolation from animal models of development, principally the mouse. However, the strong evolutionary conservation of coding sequence for developmentally important genes does not necessarily m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(80 citation statements)
references
References 54 publications
1
79
0
Order By: Relevance
“…49 Our results and published data show that the spatiotemporal regulation of human SLC25A12 expression evolved from that for the mouse ortholog, as already described for other encoding neuron-specific proteins. 50 A prenatal pattern of expression in regions involved in social cognition Quantitative ISH revealed the existence of three gradients of SLC25A12 expression in the developing neocortex, which we were able to measure. At 8 weeks, a decreasing gradient of expression from the posterior to the anterior of the telencephalon was observed, similar to that reported for several transcription factor genes, such as TBR1, EMX1 and LHX2, and for genes encoding the EphA family of receptor tyrosine kinases in fetal macaque brain.…”
Section: Discussionmentioning
confidence: 84%
“…49 Our results and published data show that the spatiotemporal regulation of human SLC25A12 expression evolved from that for the mouse ortholog, as already described for other encoding neuron-specific proteins. 50 A prenatal pattern of expression in regions involved in social cognition Quantitative ISH revealed the existence of three gradients of SLC25A12 expression in the developing neocortex, which we were able to measure. At 8 weeks, a decreasing gradient of expression from the posterior to the anterior of the telencephalon was observed, similar to that reported for several transcription factor genes, such as TBR1, EMX1 and LHX2, and for genes encoding the EphA family of receptor tyrosine kinases in fetal macaque brain.…”
Section: Discussionmentioning
confidence: 84%
“…Because embryonic expression can differ substantially between some human-mouse orthologs 14 , we carried out NIPBL in situ hybridization analyses on human embryonic tissue sections. The observed expression pattern was largely consistent with the CdLS phenotype (Figs.…”
mentioning
confidence: 99%
“…All islet cells are detectable at the end of the first trimester in humans (Piper et al, 2004), but at later stages in mice (Herrera et al, 1991). These data indicate a human-mouse temporal difference in lineage development (Richardson et al, 1997), and this is supported by differences in gene expression patterns during developmental and disease processes in these two species (Fougerousse et al, 2000). More reviews of human pancreas development can be found elsewhere (De Krijger et al, 1992;Lukinius et al, 1992;Polak et al, 2000).…”
Section: Embryologymentioning
confidence: 68%